«Data», paradigm of the cyber society - Ruani, Humberto Félix (2020)
The objective of this work, is to make an analysis of the data (dates) or information, like a right protected by the cybernetic society. All society is constructed with uses, customs and values which are importants assets to their citizens, so they must protect them. These, rights, assets are not absolute, and are changing with the course of time. Some of them because of their importance and transcendence are constituted in main paradigms of the corresponding society. From half-full of the last century, a new form to process the information (computers) has been generated, with a special language (binary), that allows the data processing (systems) in a complex and different form from the traditional one. To these high technologies, communicational triggers were added (internet), that changed the value of the information at world-wide level, and constituted them in its main paradigm